Research on the management model of distribution IoT based on cloud-edge collaboration - CHEN Chao; GONG Liwu; LUO Xin (Zhejiang dianli, 2023)
Given the excessive inference delay due to heavy computing tasks in cloud servers for distribution networks， a multi-node collaborative computing management model for distribution IoT is proposed. First， the application of edge computing in distribution networks is discussed since IoT is controllable and intelligent as well as the demand for function and transmission delay in new distribution networks. Then， the technical architecture of distribution IoT is constructed by combining the packet transport network （PTN） structure. Finally， the distribution IoT management model is constructed using the edge multi-node collaborative inference algorithm and a collaborative computing architecture model. Simulation results show that the model reduces the inference delay of cloud computing when a large number of smart device terminals in distribution IoT are connected to the network.